Padrões ecomorfológicos de Siluriformes (Osteichthyes) do riacho Caracu, Porto Rico, PR, Brasil : relações da morfologia com a distribuição longitudinal e ecologia trófica das espécies. - Pagotto, João Paulo Alves (2008)
In this study were evaluated the relationship between morphology and longitudinal distribution and trophic ecology of Siluriformes in Caracu stream (22º 45´ S/ 53º 15´ W), a tributary of Paraná River. Three sampling were realized with electrofishing between December/2005 and September/2006. Two species of Loricariidae (Hypostomus ancistroides and Hypostomus cf. strigaticeps) and four of Heptapteridae (Cetopsorhamdia iheringi, Imparfinis schubarti, Phenacorhamdia tenebrosa and Rhamdia quelen) were obtained. The Mantel test and partial Mantel test showed that despite of no relationship between morphology and longitudinal distribution, the trophic ecology showed significant relationship to the body form of species, independently of the phylogeny. Subsequently, the principal component analysis demonstrated the segregation of two ecomorphological groups. At one extreme there were the Loricariidae (detritivores) with depressed bodies, long peduncles and well developed fins (exception the anal fin), while at the other there were the Heptapteridae (omnivores and insectivores) with high compressed bodies, well developed anal fins and relatively bigger mouths. The canonical discriminant analysis using ecomorphological variables predicted successfully all trophic guild components and revealed an ecomorphological divergence between omnivores and insectivores. Therefore, the present study demonstrated that the Siluriformes of Caracu stream are structured ecomorphologically, with the morphology being a good quality tool to predict the trophic ecology of species.